Ethical Leadership and Employees’ Creativity: The Mediating Role of Organizational Pride - AL-HARAISA, Yazan Emnawer (Foundations of management, 2024)
The purpose of the current study is to examine the mediating role of organizational pride on the relationship between ethical leadership and employees’ creativity. Using a convenience sample of (130) managers, heads of the department, and their employees from private hospitals in Jordan, the data were gathered by questionnaire. The current study adopted a quantitative approach. Furthermore, structural equation modeling (SEM) was used to test the study hypotheses. The current study reveals that ethical leadership has a significant and positive impact on employees' creativity. On the other side, the results of the study showed that ethical leadership has a significant and positive impact on organizational pride. Additionally, the current study also showed that organizational pride has a significant and positive impact on employees' creativity. Finally, it has been found that there is a mediation impact on the relationship between ethical leadership and employees' creativity. These findings may help the leader to focus heavily on organizational pride to foster the relationship between ethical leadership and employees’ creativity.